Reforming port processes in India for logistics efficiency. - Mitra, Sabyasachi; Banerjee, Pritam; Sanganeria, Atul; Pratap, Mayank; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This brief offers policy recommendations for streamlining and digitizing port logistics and operations in India based on findings of a study conducted on the Jawaharlal Nehru and Vishakhapatnam ports.
Keywords: Transportation; Freight and freightage; Shipping -- Economic aspects -- India; Electronic book